Responses and Nonresponses in a Bound Morpheme Elicitation Task by Deaf and Hard of Hearing Children. - Ingvalson, Erin M.; Grieco-Calub, Tina M.; VanDam, Mark; Perry, Lynn K. (Journal of Speech, Language & Hearing Research, 2026)
Purpose: We aimed to explore the rates of bound morpheme production at two time points (T1 and T2) by deaf and hard of hearing (DHH) preschoolers and their typically hearing (TH) peers. We further sought to describe the rates and types of unscorable responses children produced. Method: Sixty-four DHH preschoolers and 66 TH preschoolers participated as part of a larger, ongoing longitudinal study. Children were given the Test of Early Grammatical Impairment (TEGI) screener, which elicits productions of the third-person singular present and past tense. TEGI screeners were given twice, spaced 6 months apart. Results: TH children produced significantly more singular present-tense and regular past-tense morphemes than cochlear implant (CI)–using children at both time points; hearing aid–using children were not significantly different from TH or CI users. All children were more accurate with the regular past tense at T2 than at T1. No interactions were significant. Examining the types of unscorable responses indicated that the DHH children were more likely to echo the prompt than TH children, particularly at T1. Conclusions: Assessments that elicit bound morpheme productions may not best capture DHH children’s morphological sensitivity. When language samples are not feasible, receptive tasks may be a good alternative to probe children’s knowledge.